Opportunities of Thai Fruits in People’s Republic of China and Preparation for Exports and Customs Clearance - KHUMRAT, SUPAWADEE; Sripontong , Maturapoj; Rungruang, Siriwut (Business Administration and Management Journal Review, 2023)
This article aims to 1. Analyzed the opportunities of the Thai fruit market in China market by using PEST Model, which is a strategic tool for analyzing external factors affecting the fruit export business in China in 2016-2022, consisting of 4 factors: 1.1 Political and legal factors related to fruit exports include China Open-door Policy and Free Trade Agreement 1.2 Economic factors found that the economy in China has continued to expand. The population have more income and purchasing power. Therefore, it is an opportunity for exporters. 1.3 Social and cultural factors found that consumer behavior in China has changed, by choosing products that focus on quality , culture and beliefs influence to purchasing decisions. 1.4 Technology factor, China is now becoming a technology leader in the industries and consumption sectors. 2. To prepare exports and customs clearances. The exporter must request a certificate from the relevant authority and select customs broker based on service quality as an important factor.